POTENSI SUMBER MATA AIR KLEBUTAN SEBAGAI ELEMEN DAYA TARIK WISATA RELIGI YANG BERBASIS KERAKYATAN DAN BERKELANJUTAN PADA OBYEK WISATA TAMAN MUMBUL DI DESA SANGEH KABUPATEN BADUNG - I Wayan Arka (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Tourism development is part of national development. Balinese tourism is based of the concept of life of Hindu religious community called Tri Hita Karana. Implementation of this concept can not be separated from the role of Desa Adat in the Sabha Desa decision (village meeting) together with Krama Desa (local community). The existence of the community is very important to play an active role in maintaining its sanctity and able to manage well in order to remain steady, sustainable, to make DTW Religious Tourism Based on Community andSustainability. Partnerships and involvement in business with lokal communities (in traditional villages) need to be built fairly and equitably. Form of activity, creativity, innovation and community cooperation is needed in building their Village Potention, so that the existing assets can be well managed and useful for present and future life. Development of religious tourism potential on Taman Mumbul attractions, believed by the community to be able to provide safety, health and together welfare. These kind of tourism is a special interest tourism called religious spiritual tourism.